MEMPERTAHANKAN KEHIDUPAN TOLERANSI BERAGAMA SUKU TENGGER BROMO MELALUI PERAN TOKOH AGAMA - Setiawan, Rudi (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2023)
This article discusses maintaining the life of religious tolerance of the Tengger Bromo tribe through the role of religious figures. Tolerance is very necessary in the face of the nation and regions that are patterned variously in religious aspects, as is the case in the Tengger Bromo tribe, in Indonesia. Religious diversity that arises in society has the intention of civil conflict and intolerance issues. Maintaining harmony and maintaining the principle of tolerance between religious people which is accommodated through the role of religious leaders is an important part of the life of the Tengger community. This research uses qualitative research with a type of case study approach. The purpose of this study is to explain religious tolerance and the role of figures in relations between religious people in the Tengger Bromo community. The results of this study show that religious tolerance is established and contained in a life of value through the form of community cooperation, partisanship, awareness of the recognition of individual or group religious rights, as well as the maintenance of distinctive traditions that continue to run and are knitted through emotional ties that are useful in forming unity solidarity in social, cultural, and religious life. Efficient consolidation by the role of religious leaders maintains religious tolerance with open communication in response to the issue of relations between people and as an alignment of public knowledge for a harmonious and harmonious life